Influence of the diameter of nanoparticles in complexes metal-aquatic humic substances - Vieira, Daniele Frasson [UNESP]; Furquim, Nicolas Henrique [UNESP]; Botero, Wander Gustavo; De Oliveira, Luciana Camargo; Goveia, Danielle [UNESP] (Ecletica Quimica, 2018)
Nanoparticles are emerging as the object of research in all fields of chemistry, their special properties are matter for concern, because a considerable portion of these materials are eliminated in the environment. A key point of the discussion is how nanoparticles will interact with other components in natural waters. In this project, the main objective will be to study the interactions of nanoparticles with metallic ions in the presence of humic substances in environmental systems. It is intended to differentiate free and labile metal ions using nanoparticles and organic matter in the form of aquatic substances (extracted from samples collected on the coast of São Paulo). It is intended to simulate the environmental systems and to verify the competition between the complexants. The differentiation of the free and complexed ions will be done using an ultrafiltration system equipped with polyethersulfone membrane (1KDa) and determination of the metals by atomic absorption spectrometry with flame atomization.
Keywords: Metal ions; Nanoparticle influence; Nanoparticles; Water systems